2007
DOI: 10.1371/journal.ppat.0030077
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomic Modifications Predict Active Promoters and Gene Structure in Toxoplasma gondii

Abstract: Mechanisms of gene regulation are poorly understood in Apicomplexa, a phylum that encompasses deadly human pathogens like Plasmodium and Toxoplasma. Initial studies suggest that epigenetic phenomena, including histone modifications and chromatin remodeling, have a profound effect upon gene expression and expression of virulence traits. Using the model organism Toxoplasma gondii, we characterized the epigenetic organization and transcription patterns of a contiguous 1% of the T. gondii genome using custom oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
141
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(152 citation statements)
references
References 40 publications
(58 reference statements)
9
141
0
2
Order By: Relevance
“…The biological meaning of this observation is still unknown but it was found that deacetylated histone-containing sites are associated with a reduced level of expression of the neighboring genes, suggesting a polar effect of these epigenetic modifications on the surrounding genes (e.g. bradyzoite-specific BSR4-related genes, Saksouk et al, 2005;Gissot et al, 2007). Thus, several coexpressed genes are clustered into eu-or heterochromatin domains, which suggest that chromatin, can be further divided into separate domains.…”
Section: Th Emop August 2008mentioning
confidence: 98%
See 4 more Smart Citations
“…The biological meaning of this observation is still unknown but it was found that deacetylated histone-containing sites are associated with a reduced level of expression of the neighboring genes, suggesting a polar effect of these epigenetic modifications on the surrounding genes (e.g. bradyzoite-specific BSR4-related genes, Saksouk et al, 2005;Gissot et al, 2007). Thus, several coexpressed genes are clustered into eu-or heterochromatin domains, which suggest that chromatin, can be further divided into separate domains.…”
Section: Th Emop August 2008mentioning
confidence: 98%
“…1). Besides, some of these marks on histone have been shown to have evolutionarily conserved roles in transcription regulation (Saksouk et al, 2005;Sullivan & Hakimi, 2006;Gissot et al, 2007). Physical maps describing the exact position of each modified histone on the genome provides an invaluable tool to analyze its complex regulatory circuits involved in the gene expression.…”
Section: Th Emop August 2008mentioning
confidence: 99%
See 3 more Smart Citations